Is substitutability the new efficiency? Endogenous investment in the elasticity of substitution between clean and dirty energy - Fabian Stöckl (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
When analyzing potential ways to counter climate change, standard models of green growth abstract from investment in substitutability between "clean" and "dirty" energy inputs. Instead, they rely on the assumption that efficiency with respect to fossil fuels can be increased perpetually. However, this is not in line with observed firm investment behavior and the limits to efficiency imposed by thermodynamic laws. In this paper, I develop a growth model that explicitly accounts for endogenous investment to increase input substitutability, in addition to investment in efficiency. The model predicts that, for a growing economy, there is always investment in both substitutability and efficiency, even without a carbon cap and with non-infinite fossil fuel prices. Most importantly, in the long-run, with sufficient investment in substitutability, fossil fuels become inessential for production. Moreover, the model predicts a declining income share of fossil fuels, an outcome not featured by standard models based on purely efficiency-enhancing technological progress. Overall, the model generates an endogenous path of transition from an economy characterized by a low elasticity of substitution to one characterized by a high elasticity. In doing so, it still nests the results derived from a purely efficiency-based directed technical change framework as a special case. In addition, this paper analyzes the scope for policy intervention, showing that even a temporary subsidy/tax can trigger a full transformation toward green growth.
Keywords: Q20; Q30; O30; O40; 330; elasticity of substitution; endogenous (sigma-augmenting) technological change; growth; investment incentives; climate policy; decarbonization